Sources and Resources: Photography and Archives in Africa - (:unkn) unknown (My University, 2018)
With contributions by Sandrine Colard, Katharina Greven, Lena Naumann, Siegrun Salmanian & Nadine Siegert, Marian Nur Goni, Siona O’Connell, Érika Nimis, Anthony Downey & Akram Zaatari.
Keywords: African Research